OPTIMIZING AMOUNT AND IDENTIFICATION OF YEAST IN SALAK YEAST WATER (Salacca edulis Reinw cv Pondoh) - Khumaira, Annisa; Annaziha, Salma; Baihaqi, Muhammad Azizan Azmani; Anindita, Nosa Septiana; Bimantara, Arif; Probowati, Wiwit (BRIN - Badan Riset dan Inovasi Nasional, 2024)
Salak fruit is a tropical fruit spread across Southeast Asia and can potentially be a source of natural yeast by processing fruit yeast water. Salak fruit is known to be rich in carbohydrates, making it a potential natural habitat for microbial communities, especially yeast. This research aims to optimize the growth of yeast in the salak yeast water system by varying the sugar concentration treatment, the composition of the amount of fruit flesh, and the fermentation time, as well as identifying the yeast in the salak yeast water. The method used is to count the number of yeast colonies using the Total Plate Count method. The most optimal treatment results are then tested for pH, total sugar, alcohol, isolation and yeast identification. The research results showed that the composition of salak meat was 30%, adding 1% sugar, and fermentation for 6 days resulted in the most optimal growth of the microbial community with an amount of 3.1×10⁶ cfu/ml. The pH test showed a result of 3.01, the alcohol content, namely ethanol, was 0.066855%, no methanol was detected, the total sugar test result in the yeast water was 2.08%, and it was identified in the yeast water that there were Hanseniaspora opuntiae and Candida sorboxylosa. The results show that salak yeast water (Salacca edulis Reinw cv Pondoh) can be used as a yeast water product to ferment food.